Changes in COVID-19 vaccine hesitancy at different times among residents in Guangzhou, China - Chen, Lu; Li, Zhi; Lu, Xiaoxiao; Deng, Yibin; Lu, Katie; Li, Tiegang; Lu, Ling; Wang, Zhiwei; Lu, Jiachun (Frontiers in Public Health, 2023)
Background Vaccination as a fundamental pillar of promoting public health and interest is critical to limiting the COVID-19 pandemic. However, many citizens are still hesitant about this epidemic prevention measure. This article aimed to understand the COVID-19 vaccination and hesitancy rates among Guangzhou residents at different points in time as well as to explore the relevant factors that cause vaccination hesitancy. Methods We conducted a total of nine cross-sectional surveys by enrolling 12,977 questionnaires among Guangzhou residents through the online survey software called “WenJuanXing” between April 2021 and December 2022, and residents made their choices by judging their willingness to vaccinate. These surveys collected data on the participants' sociodemographic characteristics, vaccination status, vaccine hesitancy, and factors influencing this hesitancy. The Chi-squared test was used for univariate analysis and the multivariate logistic regression model was used to further adjust the influence of the confounding factors to evaluate the main factors affecting the hesitancy of the COVID-19 vaccine at different periods. Results Over the course of 2021–2022, a total of 12,977 residents in the study area were surveyed. The vaccine hesitancy rates fluctuated over time. From April to June 2021, the vaccine hesitancy rate decreased from 30% to 9.1% and then increased to 13.7% in November. However, from April to December 2022, the hesitancy rate continued to rise from 13.4% to 30.4%. Vaccination rates, the epidemic waves of COVID-19, and changes in policies may all be possible factors that contributed to these fluctuations in vaccine hesitancy rates. We found statistically significant correlations between factors, such as residence, education, and occupation, and vaccine hesitancy at certain points of time. The results of the surveys in April and June 2021 showed that rural residents showed higher vaccine hesitancy rate than urban residents. Their lower education level was associated with higher vaccine hesitancy. Workers and farmers are more likely to have vaccine hesitancy than people with other occupations. The univariate analysis showed that people with underlying medical conditions and lower perceived health status were more likely to experience vaccine hesitation. Logistic regression analysis revealed that the health status of individuals is the most important factor leading to vaccine hesitancy, and residents' underestimation of domestic risks and overconfidence in personal protection measures were also contributing factors. At different stages, vaccine hesitancy among residents was related to vaccine side effects, safety and efficacy, convenience fluctuation, and various factors. Conclusion In the present study, we found that vaccine hesitancy did not display a consistent downward trend but it fluctuated over time. Higher education, residing in urban areas, lower perceived disease risk, and concerns about the vaccine's safety and side effects were risk factors for vaccine hesitancy. Implementing appropriate interventions and educational programs tailored to address these risk factors may prove to be effective in enhancing public confidence on vaccination.